Silicon as a beneficial nutrient for productivity augmentation and abiotic/biotic stress tolerance in sugarcane - Misra, Varucha; Mall, A.K.; Ansari, Shamim Akhtar; Raheem, Abdul; Tripathi, M.K.; Ansari, Mohammad Israil (Biocatalysis and agricultural biotechnology, 2023)
Climate change-induced biotic and abiotic stresses pose significant challenges to sugarcane cultivation, threatening global production. Losses in sugarcane production and productivity are exacerbated under abiotic and biotic stress conditions. The application of silicon, an abundant and versatile element, has emerged as a promising solution, either as soil fertilizer or foliar spray. The silicon supplementation on sugarcane exposed to abiotic and biotic stressors has gained attention due to the substantial enhancement of sugarcane yield and related traits. Notably, silicon application imparts resistance against water stress, cold temperatures, arthropod invasion, and fungal infections in sugarcane crops. Through an in-depth analysis of existing studies, this review underscores the consistently positive effects of silicon fertilization on sugarcane, offering insights into its mechanisms of action and potential applications. Emphasizing the need for continued investigation, it discusses avenues for refining silicon-based interventions, optimizing application methods, and integrating silicon supplementation with other agricultural practices. Additionally, the review addresses gaps in current knowledge, encouraging further studies to elucidate the molecular and physiological basis of silicon-mediated stress tolerance in sugarcane. This review paper offers valuable insights to researchers, agronomists, and policymakers, guiding the development of sustainable strategies to ensure the resilience and productivity of sugarcane crops in the face of evolving environmental challenges.